OLIGARK SEBAGAI RENT SEEKER: HARUSKAH? - Vellayati Hajad (Universitas Teuku Umar, 2017)
This article talks about the emergence of oligarchs in West Aceh district. Oligarch is referred to here are those who dominate limited resources. Furthermore, this paper aims to examine the practice of rent seeking that played by businessmen after the local election process. Based on the study it can be concluded that; First, there is a strong connection between businessmen and candidates; clientelistic both emerging businessman who work on the basis of patronage; and third the practice of rent seeking in the distribution of government projects. Keyword: oligarch, rent seeker, local election, democracy